HUBUNGAN TINGKAT KONSUMSI MAKANAN TINGGI OMEGA 3 DAN OMEGA 6 TERHADAP PRESTASI BELAJAR PELAJAR SMP - Thoriq Setya N (2023)
Abstract Learning achievement is a benchmark to find out how well students understand the material that has been given. There are many factors that influence academic achievement, one of which is intake of omega 3 and omega 6 fatty acids. However, junior high school students often lack nutrient intake, including intake of omega 3 and omega 6 fatty acids. This research was conducted to determine the relationship between high food intake omega 3 and omega 6 on learning achievement of junior high school students. This research is an observational analytic research with cross sectional design with 75 respondents using simple random sampling technique. Based on the results of the study, it was found that respondents with low achievements were 8% and 92% with high achievements. While the results of the intake of omega 3 less respondents were 8% and the rest were good 92%, while the results of intake of omega 6 were less respondents as much as 2.7%, sufficient intake of omega 6 was 10.7% and intake of omega 6 was more 86.7%. The results of the bivariate test using the Fisher's exact test showed that there was a significant relationship between omega 3 intake and learning achievement (p = 0.00) and there was a significant relationship between omega 6 intake and learning achievement (p = 0.02). So it can be concluded that there is a relationship between intake of omega 3 and omega 6 on student achievement at SMP 160 Jakarta. Keywords: Intake of Omega 3, Intake of Omega 6, Learning Achievement